Assessment of Health Information System Implementation Using PIECES Method: A Case Study of SI-KERIS at RSUD Dr. R. Soedjono Selong - Yan Sitaristy Citraningtyas; Edy Susena (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the implementation of the SI-KERIS application at RSUD Dr. R. Soedjono Selong using the PIECES framework, which covers aspects of Performance, Information, Economy, Control, Efficiency, and Service. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation review. The findings indicate that SI-KERIS effectively processes inpatient service indicators such as Bed Occupancy Rate (BOR), Average Length of Stay (AvLOS), Turn Over Interval (TOI), Bed Turn Over (BTO), Gross Death Rate (GDR), and Net Death Rate (NDR). However, challenges were identified regarding network connectivity, data integration, and the absence of a backup system. These results underscore the need to enhance system interoperability, strengthen data security, and provide user training. The application of the PIECES framework offers strategic insights to identify improvement areas and optimize hospital health information systems